Etika Menulis dengan Cahaya - Widyatmoko, Agus Toto (Interaksi: Jurnal Ilmu Komunikasi, 2016)
Abstract :The mass media had great influence in conveying a message against their common. The values of the message was set out in the text and images are presented by the media. The message may contain meaning positive and inspiring in describing events, so that is not interfere psychological of audience. Â In the context of photojournalism, the expression that the power of the image can be far beyond the message conveyed through text. Because the meaning of the message, the essence of photojournalism must pay attention to the rules of journalism were set in the Press Law and the Code of Ethics of Journalism. An understanding of the ethics of photojournalism is not only for internal media, but also to a audience. Thus, the public can judge the mindset of media displaying photographic work does pay attention to aesthetic aspects or ignore the rules of journalism.Â Keywords: Photojournalism, Press Law, the Code of Ethics Journalism, the Power of Image